1978
DOI: 10.2478/cttr-2013-0449
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and ldentification of 2,6- Dimethyl- and 2,2,6 -Trimethyl-4-piperidone, Artifacts Produced by the Reaction of Cigarette Smoke Condensate and Acetone

Abstract: Cigarette smoke condensate (CSC) processed with acetone was found to contain 2,2,6-trimethyl-4-piperidone and the cis and trans isomers of 2,6-dimethyl-4-piperidone. The compounds were found to be artifacts formed by the reaction of the smoke components ammonia and acetaldehyde with the solvent acetone. Conditions which affected the yield of the artifacts from the processed CSC include pH, temperature, reaction time, and levels of ammonia and acetaldehyde present in CSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For the purpose of this study, similar 13 C NMR techniques have been applied that will be shown to provide meaningful information on the nature of the structures of the components that result from reactions of HQ and Q within smoke matrices. Thus, based in part on the information surrounding the characteristics of mainstream cigarette smoke as portrayed by hydroxybenzenes, the chemical complexity of mainstream cigarette smoke, as well as smoke chemistries disclosed within additional reports (38,39), the dynamic reactivity of mainstream cigarette smoke would seem to have been confirmed and well documented. In this report is described yet another reaction between reasonably well known cigarette smoke components.…”
Section: Resumementioning
confidence: 99%
“…For the purpose of this study, similar 13 C NMR techniques have been applied that will be shown to provide meaningful information on the nature of the structures of the components that result from reactions of HQ and Q within smoke matrices. Thus, based in part on the information surrounding the characteristics of mainstream cigarette smoke as portrayed by hydroxybenzenes, the chemical complexity of mainstream cigarette smoke, as well as smoke chemistries disclosed within additional reports (38,39), the dynamic reactivity of mainstream cigarette smoke would seem to have been confirmed and well documented. In this report is described yet another reaction between reasonably well known cigarette smoke components.…”
Section: Resumementioning
confidence: 99%
“…Acetone and its mixtures, however, caused discoloration and degradation of nornicotine after storage for 12 h, very probably because of chemical reaction between the secondary amine group on the pyrrolidine ring of nornicotine and the carbonyl group of acetone. With an extra pair of electrons on the nitrogen the pyrrolidine ring has the normal basicity and the nature of a secondary aliphatic amine [9,10]. Because of incomplete miscibility with the aqueous ammonia solution use of 100% dichloromethane or hexane and resulted in a low recovery of some alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…Gel chromatography of dry condensates revealed polymerization being a factor in the changes of condensate composition due to aging. In view of the fact that acetone had become a preferred solvent for taking up cigarette smoke condensate it is noteworthy that EINOLF et al (542) identified three methylated piperidones, which were formed as artifacts by reactions between the solvent, acetone, and two smoke constituents, acetaldehyde and ammonia.…”
Section: The Smoking Machine Sibata Sg-200mentioning
confidence: 99%